NATURE OF TEACHERS MOTIVATION TECHNIQUES ADOPTED BY DIFFERENT CATEGORIES OF PRIVATE SCHOOLS - Dr.S.A.Mohamed Ali, Ms.Vijaya Lakshmi (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
Teachers’ motivation and successful retention of teachers for a longer period is purely depends on the intrinsic, extrinsic and altruistic motivation factors. This research article aims to analyse nature of teachers’ motivation technique adopted by different categories of schools (based on the ownership pattern) in Coimbatore city. Convenience sampling technique was applied for collection of data from the targeted sample group of teachers i.e., 100 teachers from each category of private schools. Researcher succeed in collecting 390 filled questionnaires. Data analysis indicates that the private trust schools and privately owned educational institution (entrepreneurs) attempts to keep their teachers motivate through provision of right value of monetary benefits (salary and other perks). And this motivation factor slightly varies and lower in the specific community owned schools and the schools that are run by the minority communities. At the next level, with slight differences in the percentage values, it was observed that all categories of school aim to reduce the stress level of teachers and ensure that they work in a relaxed environment. At the third level all schools functioning in Coimbatore city ensure that their school has pleasant environment and enough equipped in terms of infrastructure. The private schools functioning in Coimbatore city are suggested to focus on offering the teachers training cum upskilling opportunities, that not only support them to offer their service effortlessly cum effectively, it also supports them to plan for their career progress and move-upward in their career. All categories of the private school managements are suggested to be fairness and be approachable to the teachers.